PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KINERJA DOSEN POLITEKNIK BUMI AKPELNI SEMARANG - evyana diah kusumawati; Sulida Erliyana; Iik Suryati Azizah (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2020)
The purpose of this research is to know about (1) the influence of work discipline on lecturers’ performance, (2) the influence of work environment on lecturers’ performance, (3) the influence of competence on lecturers’ performance and (4) the influence of work discipline, work environment and competence on lecturers’ performance. The population on this research is 140 lecturerss of Polytechnic Bumi Akpelni of Semarang. The data collecting method is questionnaire.The trial of this instrument was conducted on 58 lecturers of study program Port and Shipping Manajemen, Deck Department and Engine Department of Polytechnic Bumi Akpelni of Semarang. The data analysis used was multiple regression analysis technique. Before analyzing the data, an analysis of the requirements for the test is held, including the Normality, Heterocedasticity and Autocorrelation tests. The results of this research are: (1) The results of the partial t test, the value of t arithmetic> t table with a significance of 0.000 <0.05, which shows that each variable level of work discipline, level of work environment and level of competence has a significant positive effect on lecturers’ performance. It means that the higher the level of work discipline, the level of work environment and the level of competence, the higher the performance of lecturers.(2) The result on the simultaneous f test, a significance value of 0.000 <0.05 is obtained. So, that it can be said that the level of work discipline, the level of work environment and the level of competence together have a significant influence on lecturers’ performance. (3) The results of the determination test obtained are 0.874. It means that the influence of the level of work discipline, the level of work environment and the level of competence on lecturers’ performance is 87.4% while the remaining 12.6% is influenced by other factors not examined in this study. The equation of multiple regression lines Y = 0.071 + 0.487X1 + 0.222X2 + 0.307X3Keywords: Work discipline, work environment, competence and of lecturers’ performancePenelitian ini bertujuan untuk mengetahui (1) pengaruh disiplin kerja terhadap kinerja dosen, (2) pengaruh lingkungan kerja terhadap kinerja dosen, (3) pengaruh kompetensi terhadap kinerja dosen (4) pengaruh disiplin kerja, lingkungan kerja dan kompetensi terhadap kinerja dosen. Populasi dalam penelitian ini adalah Dosen Politeknik Bumi Akpelni Semarang dengan jumlah 140 orang. Pengumpulan data dilakukan dengan metode kuesioner. Uji coba instrumen ini dilakukan terhadap 58 dosen Politeknik Bumi Akpelni Semarang prodi KPN, Nautika dan Teknika, analisis data yang digunakan adalah teknik analisis regresi ganda. Sebelum analisis data terlebih dahulu diadakan pengujian persyaratan analisis meliputi uji Normalitas, Heterokedastisitas dan Autokorelasi. Hasil penelitian ini adalah: (1) Berdasarkah hasil uji t parsial diperoleh nilai t hitung > t tabel dengan signifikansi 0.000 < 0.05, yang menunjukan bahwa masing-masing variabel tingkat disiplin kerja, tingkat lingkungan kerja dan tingkat kompetensi memberikan pengaruh positif signifikan terhadap kinerja dosen artinya semakin tinggi tingkat disiplin kerja, tingkat lingkungan kerja dan tingkat kompetensi maka semakin tinggi pula kinerja dosen. Berdasarkan uji f simultan diperoleh nilai signifikansi sebesar 0.000 < 0.05, sehingga dapat dikatakan tingkat disiplin kerja, tingkat lingkungan kerja dan tingkat kompetensi bersama-sama memberikan pengaruh signifikan terhadap kinerja dosen. (3) Berdasarkan hasil uji determinasi diperoleh hasil 0.874 yang artinya adalah pengaruh dari tingkat disiplin kerja, tingkat lingkungan kerja dan tingkat kompetensi terhadap kinerja dosen adalah sebesar 87.4% sedangkan 12.6% sisanya dipengaruhi oleh factor-faktor lainnya yang tidak diteliti dalam penelitian ini. Persamaan garis regresi ganda Y = 0.071 + 0.487X1 + 0.222X2 + 0.307X3Kata kunci : Disiplin kerja, Lingkungan kerja, Kompetensi dan Kinerja dosen